2015
DOI: 10.3892/ol.2015.3347
|View full text |Cite
|
Sign up to set email alerts
|

Triplet cytotoxic chemotherapy with gemcitabine, 5-fluorouracil and cisplatin for advanced pancreatic cancer

Abstract: Abstract.In advanced or relapsed pancreatic cancer, mono-or duo-therapy has shown modest efficacy at best. The present study evaluated the efficacy of a triplet combination in relapsed or advanced pancreatic cancer. A total of 37 patients with adenocarcinoma of the pancreas in stage III/IV or with relapsed disease were treated with a gemcitabine, 5-fluorouracil and cisplatin (GFP) regimen every 3 weeks. Only 29 out of 37 patients were evaluable for response due to early treatment interruption in 8 patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…The further evidence showed that the short‐term efficacy of Gemcitabine + Cisplatin, Gemcitabine + Capecitabine were relatively better compared to other chemotherapy regimens. A combination of gemcitabine and cisplatin conceived an ORR of 11–26.4%, which was better than gemcitabine alone, and the median survival time was 7.1–8.2 months [Sohn et al, ]. Gemcitabine plus capecitabine may be considered as a standard first‐line treatment option for advanced PC, which showed a remarkable trend in improving the OS in the treatment of PC [Lee and Park, ].…”
Section: Discussionmentioning
confidence: 99%
“…The further evidence showed that the short‐term efficacy of Gemcitabine + Cisplatin, Gemcitabine + Capecitabine were relatively better compared to other chemotherapy regimens. A combination of gemcitabine and cisplatin conceived an ORR of 11–26.4%, which was better than gemcitabine alone, and the median survival time was 7.1–8.2 months [Sohn et al, ]. Gemcitabine plus capecitabine may be considered as a standard first‐line treatment option for advanced PC, which showed a remarkable trend in improving the OS in the treatment of PC [Lee and Park, ].…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the effect of TRPV6 expression on the resistance of Panc-1 cells to three chemotherapeutic drugs: gemcitabine, cisplatin, and 5-FU. These drugs are commonly used in the treatment of pancreatic cancer, but often fail to achieve satisfactory outcomes due to the development of drug resistance [31][32][33][34]. We found that TRPV6 knockdown sensitizes Panc-1 cells to 5-FU treatment.…”
Section: Discussionmentioning
confidence: 78%